Resistance Pattern acquired by nosocomial pathogens: a plasmid profile study - Smaranika Pattnaik, Monalisa Pradhan and Manoj Narayani (Journal of Applied Pharmaceutical Science, 2013)
Nosocomial (Hospital acquired) bacterial strains were isolated from the premises of V.S.S. Medical College and Hospital, Burla, Odisha. The strains were preliminarily characterized by using “Routine diagnostic methods” and were identified as Pseudomonas sp., Klebsiella sp., Bacillus sp. respectively. The resistance nature of all the nosocomial strainswere clearly evident from the “Sensitivity testing” by following Kirby-Bauer method. A plasmid profile study revealed that all the isolated and identified strains were harboured with plasmids. Provisionally a concluding statement was given for the possible role of plasmids in drug resistance acquired by nosocomial bacterial strains.
Keywords: Nosocomials, drug resistance, plasmid.&